Spatial Distributions and Environmental Significance of Nitrogen in Sediments of Two Typical Urban Shallow Lakes in Southern Fujian, P.R. China - Guo, Pei-yong; Wang, Jin-ming; Xu, Peng-yu; Zhao, Xiao-yan; Chang, Chein-chi (Asian Journal of Chemistry, 2011)
In this article, contents and distributions of N-forms in sediments from two typical urban shallow lakes in southern Fujian province of China were studied with the purpose of evaluation of nitrogen contamination and its risk to aquatic systems. Meanwhile, from different perspectives, relevant factors and environmental significance were also analyzed. The main results are as follows, (1) Non-transferable nitrogen (NTF-N) is the dominant form in total nitrogen; transferable nitrogen (TF-N) accounts for 17.64 and 17.20 % of total nitrogen, respectively. (2) The contents of IEF-N, WAEF-N and SOEF-N are positively correlated with total organic carbon in sediments. Also, the contents of IEF-N and SOEF-N are positively correlated with chlorophylla of the overlying water. (3) The four forms of TF-N, reciprocally interacted, are not obviously affected by temperature, pH and dissolved oxygen in the overlying water. Nitrogen in sediments is a good indicator of lake eutrophication, therefore, it has a very important environmental significance.